Sikap Ibu Terhadap Larangan Sunat Pada Anak Perempuan Di Kelurahan Sekumpul Kabupaten Banjar - Faizah Wardhina; Brigitta Susanta (HB PRESS, 2017)
Banjarese consider female circumcision is a habit that can not be left behind because one of the religious commands, especially Islam. PERMENKES No.6 year 2014 determined to revoke PERMENKES No.1636/MENKES/PER/XI/2010 which is set the procedure of female circumcision, with consideration of female circumcision is not currently a medical act because the implementation is not based on medical indication and has not proven useful for health. This research aims to determine the attitude of the mother against the prohibition of circumcision in girls in Kelurahan Sekumpul Kabupaten Banjar. This research used descriptive method with population of all mothers who have daughters aged 0 - 59 months in Kelurahan Sekumpul. Sampling method using accidental sampling technique, obtained sample 40 people. The variables studied were mothers attitudes toward the prohibition of circumcision on daughters, obtained data using questionnaires. The research showed that more mothers had positive attitudes toward the prohibition of circumcision on daughters 37 respondents (92,5%) while negative ones were only 3 (7,5%). Most respondents were positive about the prohibition of female circumcision (92,5%). It is expected that the mother should compensate for the attitude that accepts the ban with the uncircumcised behavior of her daughter